Answer:
![x=2, y=-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/jl2fh7rs7t6gtjnfrgug78ke7yaio81dqw.png)
Explanation:
Multiply the first equation by -1 to have your two equations now be:
![-3x+4y=-18](https://img.qammunity.org/2023/formulas/mathematics/high-school/jn6uz6e4yxi6i1zw8fdojmmzqxoml61dxg.png)
![3x-y=9](https://img.qammunity.org/2023/formulas/mathematics/high-school/dawq1ouj7s337xalc3gt0arnjbskvlqbup.png)
Then add the two equations to get:
![3y=-9](https://img.qammunity.org/2023/formulas/mathematics/high-school/qwanl9p0u76f3nx7xxc1fjzi8fw0vmz42r.png)
Divide both sides by 3 to reach:
![y=-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/pv8pm72wtjhyefrexn9uy6t2nsbsg45q1u.png)
Then substitute
for
in either of the two first original equations and solve for x, getting:
![x=2](https://img.qammunity.org/2023/formulas/mathematics/college/6ij5lvx45qkbn22ki7umkb6rdcr9rugcgd.png)
Hope this helps :)